(untitled) (Revista Teoria e Evidência Econômica, 2020)
With high-interest rates being the norm as this is written, Brazil has little reason to be worried about liquidity traps which have recently resurged in international economic literature. Studies intertwining the Brazilian scenario with them have been sparse. However, Brazil’s legislative framework raises alarms: fiscal legislation with the principle of legality as applied in the Brazilian scenario seems to form a problematic situation. The goal of this work is to alert one to the possible undesirable effects, caused by short-sighted legislation should a liquidity trap occur in Brazil, although it does not seem to be a concern in the short term. The methodology we use is descriptive and bibliographical, through a revision of the literature. We conclude that if the argument of a significant part of the literature is thought to follow, the country may find itself in a worrisome scenario.